Study of Thermodynamic Properties of Bi-Pb Liquid Alloy - Bohora, Chandra Kumar; Koirala, Ishwar (Journal of Nepal Physical Society, 2022)
We have used quasi-lattice theory to describe the mixing behavior of Bi-Pb liquid alloys at a temperature of 700K by computing thermodynamic functions and structural functions. The thermodynamic functions includes free energy of mixing (GM), activity (a), heat of mixing (HM), entropy of mixing (SM). The structural functions includes concentration fluctuation in the long-wavelength limit (Scc(0)) and chemical short range order parameter (α1). Most of the computed values are in good agreement with the experimental data. The pair-wise interaction energies between the species of the liquid alloys play important role and are found to temperature dependent. Theoretical analysis suggests that Pb3Bi complex exists in the liquid state at 700K. And, it has hetero-coordination (i.e. ordering) nature but is of weakly interacting in nature.